The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0022112006003211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature-dependent solubility on the onset of thermosolutal convection in a horizontal porous layer

Abstract: We consider the onset of thermosolutal (double-diffusive) convection of a binary fluid in a horizontal porous layer subject to fixed temperatures and chemical equilibrium on the bounding surfaces, in the case when the solubility of the dissolved component depends on temperature. We use a linear stability analysis to investigate how the dissolution or precipitation of this component affects the onset of convection and the selection of an unstable wavenumber; we extend this analysis using a Galerkin method to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 29 publications
2
55
0
Order By: Relevance
“…Indeed, RT and DD modes are encountered in numerous systems, and it is therefore important to know whether the properties of RT and DD patterns are the same or not in reactive systems. Some theoretical works have already demonstrated that reactions can affect the stability properties of DD modes, [35][36][37] however, their active influence on nonlinear dynamics remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, RT and DD modes are encountered in numerous systems, and it is therefore important to know whether the properties of RT and DD patterns are the same or not in reactive systems. Some theoretical works have already demonstrated that reactions can affect the stability properties of DD modes, [35][36][37] however, their active influence on nonlinear dynamics remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…They considered the Darcy model to study the onset of thermosolutal convection using linear instability technique. Wang and Tan [1] extended the previous work of Pritchard and Richardson [28] in which Wang and Tan [1] considered Darcy-Brinkman model and used normal mode analysis to carry out a linear instability analysis.…”
Section: Introductionmentioning
confidence: 92%
“…More studies were carried out by Gatica et al [24,25], Viljoen et al [26] and Malashetty and Gaikwad [27]. Pritchard and Richardson [28] figured out a model similar to that of Steinberg and Brand [22,23]. They considered the Darcy model to study the onset of thermosolutal convection using linear instability technique.…”
Section: Introductionmentioning
confidence: 99%
“…They found analytical expressions for the onset of stationary and oscillatory instabilities. Pritchard and Richardson (2007) have been considered the effect of temperature dependent solubility on the onset of thermosolutal convection in an isotropic porous medium. Malashetty and Biradar (2011) have studied the onset of double diffusive reactionconvection in an anisotropic porous layer.…”
Section: Introductionmentioning
confidence: 99%